Effects of facilitation on family satisfaction and job satisfaction in the childcare industry. - Chua, Yi Ying. (2008)
Researchers have begun to examine the positive effects of work and family. In this paper, we explore the effects of supportive work environment, i.e., (a) organization support, (b) supervisor support, (c) co-worker support and (d) perceived usefulness of work-life initiatives on Family-Work Facilitation (FWF) and Work-Family Facilitation (WFF), and their effects on employee job satisfaction and family satisfaction. The data for this study was collected from 366 individuals who work in an organization in the childcare industry in Singapore. Key findings from this study demonstrate that there is a positive relationship between supportive work environment and facilitation as well as between facilitation and job and family satisfaction. Limitations, theoretical and practical implications are also discussed in this paper.